Ru-based alloy type acidic water electrolysis catalyst and application thereof
By loading oxides on the porous base and loading the RU consecutive alloy, efficient and stable RU -based acidic hydrolytic hydrolytic catalysts are prepared to solve the problem of poor stability in the acidic environment of the existing catalyst and realize it under the electrolytic conditions of the sea water water electrolyte conditions Long -term stable operation.
Patent Information
- Application Number
- CN202411682814.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-01-28
AI Technical Summary
The existing acidic water electrolytic catalysts have poor stability in acidic environments and cannot be effectively applied in the process of electrolyzing hydrogen production.
By loading the oxides of the TI, MN, or CO base on the porous base, and loading the RU consequences on the basis of it, using the water thermal and electrochemical reduction legal system catalyst.
The prepared catalyst has excellent stability and electrochemical performance. It can continue to run for 100 hours under the current density of 200mA/CM2, which is suitable for seawater electrical hydrogen.
Smart Images

Figure CN119372707A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen production by electrolysis of water, and in particular relates to the preparation and application of a Ru-based alloy type acidic water electrolysis catalyst. Background Art
[0002] The development of human society and industrial production are mainly driven by energy. However, the energy conversion and supply based on traditional fossil fuels are not only inefficient, but also face a large amount of carbon dioxide emissions, leading to serious greenhouse effects and environmental ecological problems, which pose serious challenges to the sustainable development of human society and environmental protection. Therefore, the development of low-carbon and clean renewable energy has become a consensus among countries around the world. Water electrolysis hydrogen production technology is considered to be one of the effective ways to achieve large-scale hydrogen production, especially when there is sufficient renewable energy. By electrolyzing water to decompose water into hydrogen and oxygen, it can effectively reduce carbon emissions and achieve sustainable development.
[0003] At present, most electrocatalysts used in acidic water decomposition rely heavily on Pt-based precious metals, but the scarce reserves and high cost of Pt limit its large-scale application. In contrast, Ru has become an important research object due to its relatively low price and activity comparable to Pt. At the same time, loading Ru on the surface of oxides can effectively increase the exposure of Ru active sites, reduce the amount of Ru used, and improve catalytic performance. Oxide materials also have advantages such as excellent conductivity, chemical stability and anti-toxicity in electrocatalytic applications, which can further improve the durability of catalysts. In addition, compared with traditional powder catalysts, self-supporting electrodes have better mechanical stability and the catalyst is not easy to fall off, which makes it show greater potential in practical applications.
[0004] CN118326412A discloses a method for preparing a Ru atomic gradient doped nano Co catalyst. The specific steps are: electrochemically depositing Co(OH)2 nanosheets on the surface of nickel foam, cation exchange loading Ru, annealing to obtain Ru-Co3O4 nanosheets, and electrochemical reduction to obtain Ru atomic gradient doped nano Co catalyst, which can be used for nitrate reduction to produce ammonia and has good catalytic activity, but the atomic-level Ru doping in the catalyst cannot inhibit acid corrosion of the catalyst body, making it impossible to apply to catalytic reactions in acidic electrolytes. Therefore, it is necessary to develop a self-supporting catalyst with high efficiency and stability for use in electrolysis of water to produce hydrogen under acidic conditions. Summary of the invention
[0005] The present invention provides a method for synthesizing a Ru-based alloy-type acidic water electrolysis catalyst and its application. The catalyst uses a porous substrate as a growth matrix, prepares Ti-based, Mn-based or Co-based oxides by a hydrothermal method, and then loads a Ru-based alloy, successfully developing a highly efficient and highly stable three-dimensional self-supporting porous electrode, which provides a new idea for hydrogen production by seawater electrolysis.
[0006] In order to achieve the above-mentioned object, the present invention provides a Ru-based alloy-type acidic water electrolysis catalyst, which is prepared by first loading a Ti-based, Mn-based or Co-based oxide on a porous substrate, then further loading a Ru-based metal on the basis of the above-mentioned oxide, and performing electrochemical reduction on the Ru-based metal.
[0007] Preferably, the Ti-based, Mn-based or Co-based oxide supported on the porous substrate is specifically:
[0008] A certain amount of metal salt of Ti, Mn or Co is dissolved in deionized water, ultrasonicated, and then the porous substrate and the ultrasonicated solution are transferred to a hydrothermal reactor for hydrothermal reaction;
[0009] After the reaction is completed, the temperature drops to room temperature, the product is rinsed, dried, and calcined in a muffle furnace.
[0010] Preferably, the porous substrate is selected from at least one of titanium film, nickel foam, and carbon cloth;
[0011] The Ti metal salt is at least one of titanium chloride, titanium oxalate, and tetrabutyl titanate;
[0012] The Mn metal salt is at least one of manganese chloride, manganese nitrate, manganese sulfate and potassium permanganate;
[0013] The Co metal salt is at least one of cobalt chloride, cobalt nitrate, cobalt sulfate and cobalt oxalate.
[0014] Preferably, the concentration of the metal salt solution is 0.1 to 10 mmol / L;
[0015] The hydrothermal reaction time is 3-36h, and the reaction temperature is 80℃-200℃;
[0016] The calcination temperature in the muffle furnace is 200°C-900°C, and the calcination time is 10-300 minutes.
[0017] Preferably, the Ru-based alloy is further loaded on the basis of the above oxides:
[0018] Ruthenium metal salt and other metal salts are dispersed in a solvent, and then a precursor loaded with Ti-based, Mn-based or Co-based oxides is added. After the solvent is evaporated, the mixture is calcined in a nitrogen or argon atmosphere, and after calcination, the mixture is cooled to room temperature and taken out.
[0019] Preferably, the other metal salt is selected from at least one of chloride, acetylacetonate, nitrate, oxalate and sulfate;
[0020] The mass molar ratio of other metal salts to ruthenium metal salt is 1:0.2-5.
[0021] Preferably, the solvent is selected from at least one of methanol, ethanol, acetone, n-butanol and ethylene glycol;
[0022] Preferably, the calcination temperature is 200°C-900°C, and the calcination time is 0.5-5h. It is understandable that if the calcination temperature is too low, the interaction between the Ru-based metal and the oxide substrate will be too weak, and it will be easy to fall off from the oxide surface; if the calcination temperature is too high, the interaction between the Ru-based metal and the oxide substrate will be too strong, and it will be difficult to form an alloy under the reduction current.
[0023] Preferably, the alloy is prepared by electrochemical reduction. The electrochemical reduction method not only has high energy utilization, but is also more environmentally friendly. The prepared alloy has a smaller particle size and a more uniform size. Specifically:
[0024] The Ru-based alloy-loaded oxide is electrochemically reduced in a 0.1-2 mol / L acidic electrolyte at a reduction current of -0.1 to -0.8 A to obtain a Ru-based alloy-type acidic water electrolysis catalyst. It is understandable that a reduction current that is too small or too large is not conducive to the formation of an alloy structure. If the reduction current is too low, it is not conducive to the alloying of the Ru-based metal; if the reduction current is too high, the oxide substrate may be reduced, the metal-oxygen bond in the substrate is broken, the structure is destroyed, and the overall catalytic activity is reduced.
[0025] Preferably, the acidic electrolyte is selected from at least one of hydrochloric acid solution, perchloric acid solution, sulfuric acid solution and acidic seawater solution.
[0026] The present invention also provides an application of the Ru-based alloy acidic water electrolysis catalyst described in the above technical solution in the production of hydrogen by electrolysis in an acidic medium.
[0027] Preferably, the acidic water electrolysis catalyst can operate continuously for 100 hours at a current density of 200 mA / cm2.
[0028] Compared with the prior art, the advantages and positive effects of the present invention are:
[0029] 1. The present invention uses a porous substrate to support the catalyst. The porous substrate has a high specific surface area, which is conducive to the self-growth of the catalyst. Its good electrical conductivity significantly improves the overall efficiency of the electrocatalytic reaction. Compared with powder catalysts, the catalyst that grows on the porous substrate does not need to use a binder. The use of a binder will cover the catalytic active sites and affect the catalytic efficiency. The self-grown catalyst is not easy to fall off, which is conducive to the long-term and stable progress of the catalytic reaction.
[0030] 2. The oxide-supported Ru-based alloy catalyst prepared by the present invention has a nano-sheet-shaped oxide hydrothermally grown on its surface, and the Ru-based bimetallic nanoparticles are in close contact with the oxide support, and have good resistance to shedding. After electrochemical reconstruction, the catalyst has stable performance, exhibits excellent stability and electrochemical performance in acidic solution, and can run continuously for 100 hours at a current density of 200mA / cm2.
[0031] 3. Compared with existing single metal catalysts, the present invention promotes the adsorption of intermediates through the synergistic effect of Ru and other metals, so that the Ru-based bimetallic catalyst exhibits excellent hydrogen evolution reaction performance and long-lasting stability in an acidic system. The electrochemical reduction method adopted in the present invention has low energy consumption and mild conditions. The alloy particles formed are uniform in size, highly dispersed, and have more exposed active sites. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is a SEM image of the RuFe / TiO2 catalyst of Example 1 of the present invention;
[0033] Figure 2 TEM image of the RuFe / TiO2 catalyst of Example 1 of the present invention;
[0034] Figure 3 Polarization curves of RuFe / TiO2 of Example 1 of the present invention, Ru / TiO2 of Comparative Example 1 and Fe / TiO2 of Comparative Example 2 during HER reaction in an acidic solution;
[0035] Figure 4 is the Tafel slope of RuFe / TiO2 of Example 1 of the present invention, Ru / TiO2 of Comparative Example 1 and Fe / TiO2 of Comparative Example 2 in an acidic solution;
[0036] Figure 5 This is a durability test diagram of the RuFe / TiO2 catalyst of Example 1 of the present invention in an acidic solution;
[0037] Figure 6 This is the polarization curve of the RuFe / TiO2 catalyst of Example 1 of the present invention during HER reaction in a seawater solution;
[0038] Figure 7 This is the polarization curve of the RuCo / MnO2 catalyst of Example 2 of the present invention during HER reaction in an acidic solution;
[0039] Figure 8 This is the polarization curve of the RuNi / Co3O4 catalyst of Example 3 of the present invention during HER reaction in an acidic solution.
[0040] Fig. 9 This is the polarization curve of the RuFe / TiO2 (150°C) catalyst of Comparative Example 3 of the present invention during HER reaction in an acidic solution.
[0041] Fig.10 This is the polarization curve of the RuFe / TiO2 (1000°C) catalyst of comparative example 4 of the present invention during HER reaction in an acidic solution.
[0042] Fig.11 This is the polarization curve of the RuFe / TiO2 (-0.05A) catalyst of comparative example 5 of the present invention during HER reaction in an acidic solution.
[0043] Fig.12 This is the polarization curve of the RuFe / TiO2(-1A) catalyst of comparative example 6 of the present invention during HER reaction in an acidic solution. DETAILED DESCRIPTION
[0044] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] Example 1
[0046] In this embodiment, a RuFe / TiO2 bimetallic catalyst is provided which is loaded on a titanium film and is prepared by the following steps:
[0047] Take a certain amount of tetrabutyl titanate and dissolve it in water at a concentration of 5mmol / L. After stirring until it is completely dissolved, add the titanium film and ultrasonicate. Then place the titanium film and the solution together in a hydrothermal reactor, hydrotherm at 140℃ for 8h. After the reaction cools to room temperature, rinse it repeatedly with ethanol and water, dry it at 60℃ for 30min, place it in a muffle furnace, calcine it in air at 400℃ for 2h to obtain TiO2, then take 10mg of ruthenium acetylacetonate and 10mg of iron acetylacetonate, disperse them in a mixed solution of ethanol and water, put them into TiO2, dry them, calcine them at 500℃ in a nitrogen atmosphere, and wait for them to cool to room temperature. The sample taken out is electroreduced in an electrochemical workstation, and the reduction current is -0.2A. The prepared catalyst is named RuFe / TiO2.
[0048] Example 2
[0049] In this embodiment, a RuCo / MnO2 bimetallic catalyst is provided which is supported on a titanium film and is prepared by the following steps:
[0050] Prepare 0.1mmol / L potassium permanganate solution, transfer it to the hydrothermal reactor together with the titanium film, and hydrothermally heat it at 160℃ for 8h. After the reaction cools to room temperature, rinse it repeatedly with ethanol and water, and dry it to obtain MnO2. Weigh 10mg of ruthenium acetylacetonate and 20mg of cobalt acetylacetonate, disperse them in a mixed solution of ethanol and methanol, put MnO2, dry it, calcine it at 900℃ in a nitrogen atmosphere, and wait for it to cool to room temperature. The sample taken out is electro-reduced at a current of -0.3A in an electrochemical workstation, and the prepared catalyst is named RuCo / MnO2.
[0051] Example 3
[0052] In this embodiment, a RuNi / Co3O4 bimetallic catalyst is provided which is supported on a titanium film and is prepared by the following steps:
[0053] Weigh 0.5g of cobalt nitrate, 0.55g of urea, and 0.2g of ammonium fluoride and dissolve them in 30mL of deionized water. Transfer the above solution and the titanium film to a hydrothermal reactor and react at 120°C for 8h. After the reaction cools to room temperature, rinse repeatedly with ethanol and water, dry and place in a muffle furnace, calcine at 400°C for 3h to obtain Co3O4. Weigh 10mg of ruthenium chloride and 10mg of nickel chloride, disperse them in a mixed solution of ethanol and water, put in Co3O4, dry and calcine at 200°C in a nitrogen atmosphere, and wait for cooling to room temperature. The sample taken out is electro-reduced at a current of -0.1A in an electrochemical workstation, and the prepared catalyst is named RuNi / Co3O4.
[0054] Example 4
[0055] In this embodiment, a RuFe / MnO2 bimetallic catalyst is provided which is supported on nickel foam and is prepared by the following steps:
[0056] Prepare a 0.5mmol / L mixed solution of potassium permanganate and manganese sulfate, transfer it to a hydrothermal reactor together with nickel foam, and hydrothermally heat it at 140℃ for 6h. After the reaction cools to room temperature, rinse it repeatedly with ethanol and water, and dry it to obtain MnO2. Weigh 10mg of ruthenium chloride and 10mg of ferric chloride, disperse them in a mixed solution of ethanol and methanol, put MnO2, dry it, calcine it at 600℃ in a nitrogen atmosphere, and wait for it to cool to room temperature. The sample taken out is electro-reduced at a current of -0.2A in an electrochemical workstation, and the prepared catalyst is named RuFe / MnO2.
[0057] Example 5
[0058] In this embodiment, a RuCo / MnO2 bimetallic catalyst supported on carbon cloth is provided, which is prepared by the following steps:
[0059] Prepare a 0.3mmol / L mixed solution of potassium permanganate and manganese chloride, transfer it to a hydrothermal reactor together with the carbon cloth, and hydrothermally heat it at 150℃ for 6h. After the reaction cools to room temperature, rinse it repeatedly with ethanol and water, and dry it to obtain MnO2. Weigh 10mg of ruthenium chloride and 10mg of cobalt chloride, disperse them in a mixed solution of ethanol and methanol, put MnO2 in, dry it, calcine it at 800℃ in a nitrogen atmosphere, and wait for it to cool to room temperature. The sample taken out is electro-reduced at a current of -0.8A in an electrochemical workstation, and the prepared catalyst is named RuCo / MnO2.
[0060] Comparative Example 1
[0061] Provided is a Ru / TiO2 catalyst supported on a titanium film, which is prepared by the following steps:
[0062] Take a certain amount of tetrabutyl titanate and dissolve it in water at a concentration of 5mmol / L. After stirring until it is completely dissolved, add the titanium film and ultrasonicate. Then place the titanium film and the solution together in a hydrothermal reactor, hydrotherm at 140℃ for 8h. After the reaction cools to room temperature, rinse it repeatedly with ethanol and water, dry it at 60℃ for 30min, place it in a muffle furnace, calcine it in air at 400℃ for 2h to obtain TiO2, then take 10mg of ruthenium acetylacetonate, disperse it in a mixed solution of ethanol and water, put it in TiO2, dry it, and calcine it at 500℃ in a nitrogen atmosphere to obtain Ru / TiO2.
[0063] Comparative Example 2
[0064] Provided is a Fe / TiO2 catalyst supported on a titanium film, which is prepared by the following steps:
[0065] Take a certain amount of tetrabutyl titanate and dissolve it in water at a concentration of 5mmol / L. After stirring until it is completely dissolved, add the titanium film and ultrasonicate. Then place the titanium film and the solution together in a hydrothermal reactor, hydrotherm at 140℃ for 8h. After the reaction cools to room temperature, rinse it repeatedly with ethanol and water, dry it at 60℃ for 30min, place it in a muffle furnace, calcine it in air at 400℃ for 2h to obtain TiO2, then take 10mg of ferric acetylacetonate, disperse it in a mixed solution of ethanol and water, put it in TiO2, dry it, and calcine it at 500℃ in a nitrogen atmosphere to obtain Fe / TiO2.
[0066] Comparative Example 3
[0067] Provided is a RuFe / TiO2 catalyst supported on a titanium film, which is prepared by the following steps:
[0068] Take a certain amount of tetrabutyl titanate and dissolve it in water at a concentration of 5mmol / L. After stirring until it is completely dissolved, add the titanium film and ultrasonicate. Then place the titanium film and the solution together in a hydrothermal reactor, hydrotherm at 140℃ for 8h. After the reaction cools to room temperature, rinse it repeatedly with ethanol and water, dry it at 60℃ for 30min, place it in a muffle furnace, calcine it in air at 400℃ for 2h to obtain TiO2, then take 10mg of ruthenium acetylacetonate and 10mg of iron acetylacetonate, disperse them in a mixed solution of ethanol and water, put TiO2 in it, dry it and calcine it at 150℃ in a nitrogen atmosphere, and wait for it to cool to room temperature. The sample taken out is electroreduced in an electrochemical workstation, and the reduction current is -0.2A. The prepared catalyst is named RuFe / TiO2 (150℃). Due to the low calcination temperature, the interaction between RuFe and TiO2 is weak, resulting in poor electrochemical performance.
[0069] Comparative Example 4
[0070] Provided is a RuFe / TiO2 catalyst supported on a titanium film, which is prepared by the following steps:
[0071] Take a certain amount of tetrabutyl titanate and dissolve it in water at a concentration of 5mmol / L. After stirring until it is completely dissolved, add the titanium film and ultrasonicate. Then place the titanium film and the solution together in a hydrothermal reactor, hydrotherm at 140℃ for 8h. After the reaction cools to room temperature, rinse it repeatedly with ethanol and water, dry it at 60℃ for 30min, place it in a muffle furnace, calcine it in air at 400℃ for 2h to obtain TiO2, then take 10mg of ruthenium acetylacetonate and 10mg of iron acetylacetonate, disperse them in a mixed solution of ethanol and water, put TiO2 in it, dry it, calcine it at 1000℃ in a nitrogen atmosphere, and wait for it to cool to room temperature. The sample taken out is electroreduced in an electrochemical workstation, and the reduction current is -0.2A. The prepared catalyst is named RuFe / TiO2 (1000℃). Due to the low calcination temperature, the interaction between the RuFe precursor and TiO2 is strong, and it is difficult to form an alloy under electrochemical reduction, resulting in poor electrochemical performance.
[0072] Comparative Example 5
[0073] Provided is a RuFe / TiO2 catalyst supported on a titanium film, which is prepared by the following steps:
[0074] Take a certain amount of tetrabutyl titanate and dissolve it in water at a concentration of 5mmol / L. After stirring until it is completely dissolved, add the titanium film and ultrasonicate. Then place the titanium film and the solution together in a hydrothermal reactor, hydrotherm at 140℃ for 8h. After the reaction cools to room temperature, rinse it repeatedly with ethanol and water, dry it at 60℃ for 30min, place it in a muffle furnace, calcine it in air at 400℃ for 2h to obtain TiO2, then take 10mg of ruthenium acetylacetonate and 10mg of iron acetylacetonate, disperse them in a mixed solution of ethanol and water, put TiO2 in it, dry it, calcine it at 500℃ in a nitrogen atmosphere, and wait for it to cool to room temperature. The sample taken out is electroreduced in an electrochemical workstation, and the reduction current is -0.05A. The prepared catalyst is named RuFe / TiO2(-0.05A). Due to the low reduction current, RuFe reduction cannot be driven, resulting in poor electrochemical performance.
[0075] Comparative Example 6
[0076] Provided is a RuFe / TiO2 catalyst supported on a titanium film, which is prepared by the following steps:
[0077] Take a certain amount of tetrabutyl titanate and dissolve it in water at a concentration of 5mmol / L. After stirring until it is completely dissolved, add the titanium film and ultrasonicate. Then place the titanium film and the solution together in a hydrothermal reactor, hydrotherm at 140℃ for 8h. After the reaction cools to room temperature, rinse it repeatedly with ethanol and water, dry it at 60℃ for 30min, place it in a muffle furnace, calcine it in air at 400℃ for 2h to obtain TiO2, then take 10mg of ruthenium acetylacetonate and 10mg of iron acetylacetonate, disperse them in a mixed solution of ethanol and water, put TiO2 in it, dry it, calcine it at 500℃ in a nitrogen atmosphere, and wait for it to cool to room temperature. The sample taken out is electroreduced in an electrochemical workstation, and the reduction current is -1A. The prepared catalyst is named RuFe / TiO2(-1A). Due to the high reduction current, the TiO2 substrate may be reduced during the electrochemical reduction process, resulting in poor electrochemical performance.
[0078] Performance Testing
[0079] The RuFe / TiO2 of Example 1 was observed using a scanning electron microscope (SEM) and a transmission electron microscope (TEM). Figure 1 Shown is the FESEM image of RuFe / TiO2 of Example 1. Figure 1 It shows that the prepared RuFe / TiO2 has a nanoflower-like morphology, and the nanoflower-like structure is conducive to the overflow of bubbles in the hydrogen evolution reaction and improves the electrocatalytic performance of the catalyst. Figure 2 Transmission electron microscopy shows that small RuFe particles are loaded on flaky TiO2, and the particle size is about 10nm.
[0080] At a certain current density, the smaller the overpotential value, the better the catalyst performance. -2 The overpotential at a current density of 2.5 Å was used as an indicator to evaluate the activity of the electrocatalyst. Figure 3 The LSV curves of RuFe / TiO2 prepared in Example 1, Ru / TiO2 prepared in Comparative Example 1 and Fe / TiO2 prepared in Comparative Example 2 are compared. RuFe / TiO2 is in an acidic 0.5M H2SO4+0.5M NaCl solution at 1000mAcm -2 At a current density of , the overpotential is 137 mV, which is much smaller than 333 mV of Ru / TiO2 and 429 mV of Fe / TiO2, proving that the prepared RuFe / TiO2 catalyst has excellent electrochemical performance in acidic solution.
[0081] Tafel is a parameter that reflects the catalytic mechanism. Generally speaking, a smaller Tafel slope means a faster charge transfer ability, indicating that the faster the reaction kinetics of HER in water electrolysis, the better the catalytic activity of the catalyst. Figure 4The Tafel slope comparison of RuFe / TiO2 prepared in Example 1, Ru / TiO2 prepared in Comparative Example 1 and Fe / TiO2 prepared in Comparative Example 2 is shown. In an acidic solution, the Tafel slope of the prepared RuFe / TiO2 catalyst is 31.6 mv dec. -1 Much lower than 125.8mvdec of Ru / TiO2 -1 and mv dec of Fe / TiO2 -1 , proving that RuFe / TiO2 has faster reaction kinetics.
[0082] Stability test, in order to explore the stability of RuFe / TiO2 catalyst in acidic solution, this work used chronoamperometry in acidic solution at a constant 200mAcm -2 Stability test is carried out at current density, such as Figure 5 As shown, after 100 hours of testing, the catalyst hydrogen evolution current density did not decrease significantly, indicating that the RuFe / TiO2 catalyst prepared in the present invention has good stability in an acidic solution.
[0083] Figure 6 The LSV curve of RuFe / TiO2 prepared in Example 1 in real seawater electrolyte is shown at 1000 mA cm -2 At a current density of , the overpotential required for RuFe / TiO2 is only 145 mV, proving that the prepared RuFe / TiO2 still has excellent catalytic activity in highly corrosive seawater.
[0084] Figure 7 The LSV curve of RuCo / MnO2 prepared in Example 2 in an acidic electrolyte is shown in Figure 2. -2 At a current density of , the overpotential required for RuCo / MnO2 is only 209 mV, which proves that the prepared RuCo / MnO2 has good catalytic activity in acidic electrolytes.
[0085] Figure 8 The LSV curve of RuNi / Co3O4 prepared in Example 3 in an acidic electrolyte is shown in Figure 2. -2 At a current density of , the overpotential required for RuNi / Co3O4 is only 135 mV, which proves that the prepared RuNi / Co3O4 has excellent catalytic activity in acidic electrolytes.
[0086] Fig. 9 The LSV curve of RuFe / TiO2 (150°C) prepared in comparative example 3 in an acidic electrolyte is shown at 1000 mA cm -2At a current density of , the overpotential required for RuFe / TiO2 (150°C) is 639 mV, which is much higher than that of RuFe / TiO2 in Example 1, proving that calcination at 150°C is not conducive to the formation of the alloy structure.
[0087] Fig.10 The LSV curve of RuFe / TiO2 (1000°C) prepared in comparative example 4 in an acidic electrolyte is shown at 1000 mA cm -2 At a current density of , the overpotential required for RuFe / TiO2 (1000°C) is 366 mV, which is much higher than that of RuFe / TiO2 in Example 1, proving that calcination at 1000°C is not conducive to the formation of the alloy structure.
[0088] Fig.11 The LSV curve of RuFe / TiO2 (-0.05A) prepared in comparative example 5 in an acidic electrolyte is shown at 1000 mA cm -2 At a current density of -0.05A, the overpotential required for RuFe / TiO2 (-0.05A) is 377mV, which is much higher than that of RuFe / TiO2 in Example 1, and the potential is close to that of Ru / TiO2, proving that no alloy structure is formed during reduction at -0.05A.
[0089] Fig.12 The LSV curve of RuFe / TiO2(-1A) prepared in comparative example 6 in an acidic electrolyte is shown at 1000 mA cm -2 At a current density of , the overpotential required for RuFe / TiO2(-1A) is 322 mV, which is much higher than that of RuFe / TiO2 in Example 1, proving that reduction at high current will lead to performance degradation.
Claims
1. A Ru-based alloy type acidic water electrolysis catalyst, characterized in that: The method is prepared by first loading Ti-based, Mn-based or Co-based oxides on a porous substrate, then further loading Ru-based metals on the basis of the above-mentioned oxides, and performing electrochemical reduction.
2. The acidic water electrolysis catalyst according to claim 1, characterized in that The Ti-based, Mn-based or Co-based oxides supported on the porous substrate are specifically: A certain amount of metal salt of Ti, Mn or Co is dissolved in deionized water, ultrasonicated, and then the porous substrate and the ultrasonicated solution are transferred to a hydrothermal reactor for hydrothermal reaction; After the reaction is completed, the temperature drops to room temperature, the product is rinsed, dried, and calcined in a muffle furnace.
3. The acidic water electrolysis catalyst according to claim 2, characterized in that The porous substrate is selected from at least one of titanium film, nickel foam, and carbon cloth; The Ti metal salt is at least one of titanium chloride, titanium oxalate, and tetrabutyl titanate; The Mn metal salt is at least one of manganese chloride, manganese nitrate, manganese sulfate and potassium permanganate; The Co metal salt is at least one of cobalt chloride, cobalt nitrate, cobalt sulfate and cobalt oxalate.
4. The acidic water electrolysis catalyst according to claim 2, characterized in that The concentration of the metal salt solution is 0.1 to 10 mmol / L; The hydrothermal reaction time is 3-36h, and the reaction temperature is 80℃-200℃; The calcination temperature in the muffle furnace is 200°C-900°C, and the calcination time is 10-300 minutes.
5. The acidic water electrolysis catalyst according to claim 1, characterized in that On the basis of the above oxides, the Ru-based metal is further loaded as follows: Ruthenium metal salt and other metal salts are dispersed in a solvent, and then added to a porous substrate loaded with Ti-based, Mn-based or Co-based oxides. After the solvent is evaporated, the porous substrate is calcined in a nitrogen or argon atmosphere, and after calcination, it is cooled to room temperature and taken out.
6. The acidic water electrolysis catalyst according to claim 5, characterized in that The other metal salt is selected from at least one of chloride, acetylacetonate, nitrate, oxalate and sulfate; The mass molar ratio of other metal salts to ruthenium metal salt is 1:0.2-5.
7. The acidic water electrolysis catalyst according to claim 5, characterized in that The solvent is selected from at least one of methanol, ethanol, acetone, n-butanol and ethylene glycol; The calcination temperature is 200°C-900°C, and the calcination time is 0.5-5h.
8. The acidic water electrolysis catalyst according to claim 1, characterized in that The electrochemical reduction preparation is specifically as follows: The oxide loaded with Ru-based metal is electrochemically reduced in 0.1-2 mol / L acidic electrolyte at a reduction current of -0.1 to -0.8 A to obtain a Ru-based alloy-type acidic water electrolysis catalyst.
9. The acidic water electrolysis catalyst according to claim 8, characterized in that The acidic electrolyte is selected from at least one of hydrochloric acid solution, perchloric acid solution, sulfuric acid solution and acidic seawater solution.
10. Use of the Ru-based alloy catalyst according to any one of claims 1 to 9 in electrolysis of hydrogen in an acidic medium.
Citation Information
Cited By
Preparation method of Ru-based alloyed heterojunction water electrolysis hydrogen production catalyst
CN120519895B
Electrolytic medium, acidic oxygen evolution non-noble metal manganese-based catalyst, process and application
CN120967399A